The Influence of Teaching Variations on Student Learning Motivation at SMP Negeri 1 Jeumpa - Zurida, Ulpa; Efendi, Zuhri (Journal of Education Method and Learning Strategy, 2023)
Teachers must be creative in presenting learning materials teachers must often use variations in teaching so that students are more enthusiastic in following lessons and to avoid boredom that students may experience. This study aims to determine the effect of variations in teacher teaching methods on the learning motivation of class VII students of SMP Negeri 1 Jeumpa. This research is a quantitative study with a population of 87 students consisting of 44 male and 43 female and the sample selected in this research is 30 students, the sample selection uses probability sampling technique. The data collection technique used is questionnaires and documentation while the analysis technique the data used is descriptive statistical analysis and inferential statistical analysis. The results showed that variations in teacher teaching were in the good category with a percentage of 78.22% and student learning motivation in the high category with a percentage of 77.95%. This can be proven by the results of the product-moment correlation analysis of 0.390, which means the level of relationship is in the weak category. It can be concluded that there is a positive and significant influence of variations in teacher teaching methods on the learning motivation of class VII students of SMP Negeri 1 Jeumpa.